Copyright Governance for Online Short Videos: Perspective of Transaction Cost Economics - Long, Mingxia (Frontiers in Psychology, 2022)
In recent years, copyright governance for short videos has become a hot issue of common concern in the academic community and the industry. Therefore, this study intends to explore the economic aspect of copyright governance in relation to the proliferation of infringing short videos. The short video industry of China has been taken as a case to demonstrate the copyright governance issue. Transaction cost theory has been applied to analyze the economic aspect of copyright governance in terms of four dimensions: bounded rationality, opportunism, environmental uncertainty, and asset specificity. From the perspective of transaction cost economics, the problem of short video infringement is observed to be essentially a market failure due to high transaction costs. In the short video market, substantial transaction costs are incurred in the legal transaction of copyright with these costs considered to be too high. This is especially the case when transaction costs exceed the net proceeds initially expected by short video users from the authorization, making it impossible to carry out the transaction and leading to infringement. To effectively control the copyright infringement of short videos, it is necessary to build a cross-platform information-sharing mechanism to reduce search costs, establish a unified copyright management platform to reduce coordination costs, and give full attention to the role of technical support to reduce regulatory costs.